Learning Orientation for Performance of Commercial Banks in Nepal: A Mediated Model Using Customer Relationship Management - Bista, Sarita; Devkota, Niranjan; Dhakal, Krishna; Mahato, Surendra; Paudel, Udaya Raj (Journal of Innovation in Academia, 2023)
This study aims to investigate the relationship between learning orientation and performance of commercial banks in Nepal, with a specific focus on the mediating role of customer relationship management (CRM). Using an explanatory research design and convenient sampling, data was collected from 260 participants with the aid of KOBO Toolbox. Both descriptive and inferential statistics were used to evaluate the data quantitatively. The results suggest that CRM plays a mediating role between learning orientation and banking performance, providing theoretical relevance in terms of organizational learning theory. The findings emphasize the importance of factors that empower and enable customers, such as customer skills and satisfaction, for the survival of the banking industry. Banks should prioritize excellent customer service and a positive consumer experience to enhance their performance. The concern of, this paper lies in its empirical investigation of the interrelationships between learning orientation, CRM, and performance in a specific context, as well as its theoretical and practical contributions to the field of organizational learning in the banking industry.